2001
DOI: 10.1063/1.1359161
|View full text |Cite
|
Sign up to set email alerts
|

Lithium doping of semiconducting organic charge transport materials

Abstract: We study the effects of lithium (Li) incorporation in the cathodes of organic light-emitting devices. A thermally evaporated surface layer of metallic Li is found to diffuse through, and subsequently dope, the electron transporting organic semiconducting thin films immediately below the cathode, forming an Ohmic contact. A diffusion length of ∼700 Å is inferred from analyses of the current–voltage and secondary ion mass spectrometry data. The conductivity of the Li-doped organic films is ∼3×10−5 S/cm. Photoemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
240
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(250 citation statements)
references
References 11 publications
10
240
0
Order By: Relevance
“…A similar gap state was observed in the UPS spectra of Lideposited BCP films. 25 Our data also show that the K 4s-derived band just below E F is missing in thick films. This suggests that the gap state at 0.6 eV is derived from electron transfer from K 4s to LUMO of BCP, whereas the higherlying gap state is due to split-off state of BCP HOMO ͑al-though the theoretical calculations are necessary for the detail assignment͒.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…A similar gap state was observed in the UPS spectra of Lideposited BCP films. 25 Our data also show that the K 4s-derived band just below E F is missing in thick films. This suggests that the gap state at 0.6 eV is derived from electron transfer from K 4s to LUMO of BCP, whereas the higherlying gap state is due to split-off state of BCP HOMO ͑al-though the theoretical calculations are necessary for the detail assignment͒.…”
Section: Resultssupporting
confidence: 53%
“…The gap states have been observed in BCP films on low work function metals 23,24 and Li-doped BCP film. 25 The purpose of the present study is twofold. One is to identify two types of gap states by probing the local electronic states emerged at the topmost layer.…”
Section: Introductionmentioning
confidence: 99%
“…However, this inter-diffusion process between OS and TMO thin films sometimes can be underestimated, especially when depositing TMO on OS. Previous study indicates that, after depositing metal Li on OS, the diffusion depth of Li into OS can be up to 70 nm depending on the choice of the OS [30]. If similar process exists in TMO-on-OS structure, the mechanism for the improvement of the hole current should be revised.…”
Section: Introductionmentioning
confidence: 99%
“…Doping is an important technique to control the electrical properties of polymer layers: [9,10] it increases the conductivity by several orders of magnitude even at minimal doping concentration, [9,11,12] and decreases the charge injection barrier resulting from the position shift of Fermi level relative to the carrier level. [13][14][15] Recent research has demonstrated that molecule doping-induced tail state filling can also effectively suppress geminate charge recombination at donor-acceptor interface via charge transfer excitions in bulk heterjunction (BHJ) photovoltaic. [16] Another positive effect of doping is improvement of carrier mobility attributed to deep-trap filling.…”
Section: Introductionmentioning
confidence: 99%